2005
DOI: 10.1007/s11240-004-5209-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting transformation efficiency of embryogenic callus of Upland cotton (Gossypium hirsutum) with Agrobacterium tumefaciens

Abstract: A reliable and high-efficiency system of transforming embryogenic callus (EC) mediated by Agrobacterium tumefaciens was developed in cotton. Various aspects of transformation were examined in efforts to improve the efficiency of producing transformants. LBA4404 and C58C3, harboring the pDgusBin19 plasmid containing neomycin phosphortransferase II (npt-II) gene as a selection marker, were used for transformation. The effects of Agrobacterium strains, acetosyringone (AS), co-cultivation temperature, co-cultivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 27 publications
2
77
0
1
Order By: Relevance
“…Jin et al, (2005) suggested that co-cultivation at 19 0 C for 48 hours was effective for the efficient transformation which was confirmed earlier by Dillen et al, (1997) and Sunilkumar and Rathore (2001).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Jin et al, (2005) suggested that co-cultivation at 19 0 C for 48 hours was effective for the efficient transformation which was confirmed earlier by Dillen et al, (1997) and Sunilkumar and Rathore (2001).…”
Section: Introductionsupporting
confidence: 69%
“…Co-cultivation duration was found uncertain in cotton ranging from 36 to 72 hours, mainly fascinated by the genotype variability (Sunilkumar and Rathore, 2001;Leelavathi et al, 2004;Jin et al, 2005). In present report, hypocotyls were co-cultivated in MS media (0.1 mg/l 2, 4-D + 0.5 mg/l kinetin) (Fig.…”
Section: Genetic Transformation and Regenerationmentioning
confidence: 58%
“…We first tested the pPNZIP::Cry9C vector in tobacco via Agrobacterium tumefaciens-mediated transformation. The two vectors were then introduced to two Gossypium hirsutum cultivars, YZ1 and Y668 by Agrobacterium tumefaciens-mediated transformation as previously described (Jin et al, 2005;Jin et al, 2006;.…”
Section: Vector Construction and Plant Transformationmentioning
confidence: 99%
“…However, visual markers for selection have also been used as these can increase transformation efficiency by reducing the time and the number of materials used at the screening step [7,8]. Transformants expressing reporter genes have been generated for variety of studies.…”
Section: Introductionmentioning
confidence: 99%